Eruptive history of the Karoo lava flows and their impact on early Jurassic environmental change. Issue 2 (3rd February 2017) - Moulin, M.; Fluteau, F.; Courtillot, V.; Marsh, J.; Delpech, G.; Quidelleur, X.; Gérard, M.
Abstract: This paper reports new paleomagnetic and geochronologic data from a 1500 m thick composite section belonging to the Drakensberg group, the thickest remnant of the Karoo lavas in Northern Lesotho. Flow‐by‐flow analysis of paleomagnetic directions reveals 21 magnetic directional groups, corresponding to single eruptive events, and 16 individual lava flows. The new age determinations of lava flows range from 180.1 ± 1.4 to 182.8 ± 2.6 Ma. These data, combined with previous results, allow us to propose that the main part of the Drakensberg group and the Karoo intrusive complex dated around 181–183 Ma may have been erupted over a period as short as 250 kyr and may have coincided with the two main phases of extinction in the Early Toarcian. This scenario agrees well with the discontinuous rhythm of environmental and biotic perturbations in the Late Pliensbachian‐Toarcian interval. Key Points: We combine paleomagnetism and dating to study a 1500 m thick composite section (Drakensberg group) in Lesotho We show that the major part of the Drakensberg group was emplaced over a period as short as 250 kyr We propose a scenario connecting Karoo volcanism and the major environmental perturbations of the Early Jurassic